THE TEACHING OF SPEAKING FOR JOB INTERVIEW (A CASE STUDY AT GLOBAL ENGLISH COURSE) - Naf’ihima, fika Ar-Rizqi (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Failures in job interview for Indonesian people who lack in speaking English force them to look for the solution. A lot of institutes includes of English course in Pare offers job interview program as the solution. One of the institutes who has good program in job interview is Global English course. The aim of this study to describe the teaching process of speaking for job interview at Global English, the students’ response toward the teaching of speaking for job interview, and tutor’s solution of the problems which are faced by students. To collect data from the field the researcher used interview, observation, documentation, and questionnaire. The result of this study showed that the teaching process of speaking for job interview program at Global English course had been supported by syllabus and lesson plan, the material was taken from Gramedia’s book, the media used whiteboard, the method used direct or natural method, the technique used interview and discussion technique, and the evaluation was taken on Saturday at the second week. The students had problem in constructing idea and speaking fluently but it increase their intention to follow this program until they felt confidence to face the real job interview. The tutor gave solution of students’ problem by giving them interview and discussion technique to increase their comprehension in speaking English.